PARTISIPASI MASYARAKAT DALAM PENGELOLAAN OBJEK WISATA PANTAI OHOIDERTAWUN DI KECAMATAN KEI KECIL KABUPATEN MALUKU TENGGARA - Hamdani Syahdan; Billy B. Seipalla; Yosevita Th Latupapua (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2020)
The purpose of this study was to analyze the role of Ohoidertawun villagers in the management of coastal tourism objects in the Ohoidertawun Village, Kei Kecil District, Southeast Maluku Regency. The method used in this study is a qualitative method, data collection techniques through observation, filling questionnaires, interviews, and literature studies. The results of the study explained that the role of the Ohoidertawun village community was categorized as interactive and independent participation. The form of participation is given in the form of ideas and energy. At the planning stage the community is involved in providing ideas that are made as a joint decision by the whole community to develop the potential of an existing attraction in the village into a destination that has a value of attraction for tourists. The community management stage took its own initiative to develop and carry out regional spatial planning in supporting tourism facilities by setting up shelters, food stalls, toilets, trash bins, guard posts. The tourist facilities at the Ohoidertawun beach object are carried out independently by the community themselves, without any assistance from investors or the tourism office in Southeast Maluku. While at the development stage, the community prepares cultural events that are elaborated with natural tourism, and culinary tourism becomes a tour package